2006
DOI: 10.1097/01.phm.0000219119.58965.8c
|View full text |Cite
|
Sign up to set email alerts
|

Falls Sustained During Inpatient Rehabilitation After Lower Limb Amputation

Abstract: One in five patients with lower limb amputation will likely experience at least one fall during inpatient rehabilitation, with 18% sustaining an injury. Ongoing research is required to develop appropriate intervention strategies to ameliorate the risk of falling during inpatient rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 26 publications
5
85
2
1
Order By: Relevance
“…People with a leg amputation have a greater risk of falling than the general public. The reported incidences of falls are 20% to 32% during rehabilitation [10,34] and 52% within the community [29]. The increased rate of falling in individuals with lower limb amputations is not surprising because they tend to perform very poorly on balance-related functional tests [7,8,49].…”
Section: Introductionmentioning
confidence: 99%
“…People with a leg amputation have a greater risk of falling than the general public. The reported incidences of falls are 20% to 32% during rehabilitation [10,34] and 52% within the community [29]. The increased rate of falling in individuals with lower limb amputations is not surprising because they tend to perform very poorly on balance-related functional tests [7,8,49].…”
Section: Introductionmentioning
confidence: 99%
“…10,11,40,41 Older adults aged 85 and over with amputations may have different rehabilitation goals than those aged between 65 and 88 years. A study by von Faber et al 42 showed that older adults aged 85 and over value well-being and social functioning higher than physical or psychocognitive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that 20% of service users were likely to have a fall following amputation, mostly occurring between 7 am and 3 pm, with 18% of those resulting in injury. 11 Moreover, the mean survival of older patients with lower limb amputations is very low ranging between two and five years. 12 Hence, it has been suggested that health professionals need to focus on early coordinated postamputation rehabilitation programmes to avoid risk of further deterioration and failure among older adults with amputations and increase longevity.…”
Section: Is Occupational Therapy Practice For Older Adults With Lowermentioning
confidence: 99%
“…tarafından yapılan çalışmada, 1267 ampute hastanın 260'ının en az bir kez düştüğü (%20,5) ve top- lam 374 düşmenin de 67 (%17,9)'sinin bir veya daha fazla sakatlanmayla sonuçlandığı bildirilmiştir. 13 Amputasyon rehabilitasyonu; hastanın optimal fonksiyonel kapasitesini yeniden kazandır-maya yönelik olarak, preoperatif dönemde başlayan ve postoperatif dönemde devam eden çalışmaların tümüdür. Bu dönem hastaya uygulanan çeşitli egzersizleri, mobilizasyon eğitimini, geçici ve kalıcı protez uygulamalarını içeren ve ayrıca hastada mevcut osteoartrit, osteoporoz, postür bozukluğu, kas-iskelet sistemi ağrıları gibi problem yaratan diğer durumları da değerlendiren bir süreçtir.…”
Section: Resi̇munclassified